Suppressing Interfacial Recombination with a Strong‐Interaction Surface Modulator for Efficient Inverted Perovskite Solar Cells - James McGettrick (Advanced Energy Materials, 2022)
Successful manipulation of halide perovskite surfaces is typically achieved via the interactions between modulators and perovskites. Herein, it is demonstrated that a strong-interaction surface modulator is beneficial to reduce interfacial recombination losses in inverted (p-i-n) perovskite solar cells (IPSCs). Two organic ammonium salts are investigated, consisting of 4-hydroxyphenethylammonium iodide and 2-thiopheneethylammonium iodide (2-TEAI). Without thermal annealing, these two modulators can recover the photoluminescence quantum yield of the neat perovskite film in contact with fullerene electron transport layer (ETL). Compared to the hydroxyl-functionalized phenethylammonium moiety, the thienylammonium facilitates the formation of a quasi-2D structure onto the perovskite. Density functional theory and quasi-Fermi level splitting calculations reveal that the 2-TEAI has a stronger interaction with the perovskite surface, contributing to more suppressed non-radiative recombination at the perovskite/ETL interface and improved open-circuit voltage (VOC) of the fabricated IPSCs. As a result, the VOC increases from 1.11 to 1.20 V (based on a perovskite bandgap of 1.63 eV), yielding a power conversion efficiency (PCE) from ≈20% to 21.9% (stabilized PCE of 21.3%, the highest reported PCEs for IPSCs employing poly[N,N′′-bis(4-butylphenyl)-N,N′′-bis(phenyl)benzidine] as the hole transport layer, alongside the enhanced operational and shelf-life stability for unencapsulated devices.